Levels and correlates of 24-hour movement behaviors among South Koreans: Results from the Korea National Health and Nutrition Examination Surveys, 2014 and 2015 - Eun-Young Lee; Valerie Carson; Justin Y. Jeon; John C. Spence; Mark S. Tremblay (Elsevier, 2019)
Purpose: This study aimed to examine the levels and correlates of 24-h movement behaviors (i.e., physical activity, sedentary time, and sleep), and different patterns of these behaviors in a nationally representative sample of South Koreans aged 12 years and older. This study also aimed to examine the sociodemographic correlates of 24-h movement behaviors stratified by age groups. Methods: Self-reported, repeated cross-sectional data from 10,708 participants in the 2014 and 2015 Korea National Health and Nutrition Examination surveys were used. Key variables included moderate-to-vigorous intensity physical activity, muscular strengthening exercises, walking, active transportation, sedentary time, and sleep. Sociodemographic variables included age, sex, household income, area of residence, and education level. Descriptive statistics by sex and age as well as general linear models by age group were performed. Results: The proportions of individuals meeting the moderate-to-vigorous intensity physical activity, muscular strengthening exercises, and sleep guidelines were, respectively, 21.6%, 22.1%, and 32.5% in male youth; 6.9%, 4.5%, and 22.8% in female youth; 55.5%, 30.8%, and 54.0% in male adults; 48.8%, 14.4%, and 57.6% in female adults; 44.0%, 30.6%, and 45.5% in male older adults; and 29.5%, 8.9%, and 37.3% in female older adults. The proportions of individuals showing the most ideal combinations of 24-h movement behaviors were only 3.2% in youth, 0.4% in adults, and 0 in older adults. Universally, older age, female sex, or living in metro Seoul were associated with unfavorable patterns of 24-h movement behaviors across different age groups. However, the associations of income and education with movement behaviors were mixed across age groups. Conclusion: Overall, the proportion of South Koreans with a healthy 24-h movement behavior pattern is low. The sociodemographic correlates of different types of 24-h movement behaviors should be considered when designing targeted interventions for the promotion of healthy active living for South Koreans. Keywords: 24-h movement behavior, Behavioral epidemiology, Guideline adherence, Health behavior surveillance